Aerosol-Jet-Printed Silver Nanowires as Top Electrodes in Organic Photovoltaic Devices - Arango-Marín, Vanessa; Rocha-Ortiz, Juan S.; Osterrieder, Tobias; Barabash, Anastasia; Osvet, Andres; Wortmann, Jonas; Heumüller, Thomas; Liu, Chao; Hauch, Jens; Brabec, Christoph J. (Solar RRL, 2025)
Aerosol jet printing (AJP) is an effective method for manufacturing organic photovoltaic (OPV) devices for indoor use. Its noncontact deposition, without posttreatment, and high-resolution 3D pattern printing capabilities make it ideal for using functional nanomaterial inks. This study explores ultrasonic AJP (uAJP) atomization to deposit silver nanowires (AgNW) as the top electrode layer (TEL) in OPV devices. The OPV stack is fabricated up to the hole transport layer using high-throughput screening (HTS) methodologies. Different deposition techniques, including spin-coating, blade-coating, and uAJP of AgNW inks, as well as thermal evaporation of silver, are compared. Scanning electron microscopy analysis shows that the E2X AgNW ink formed a compact TEL layer. Combining HTS setups, right selection of interlayers and uAJP method, automated, solution-processed OPV devices with power conversion efficiencies of 9.54% on an active layer of 0.0232 cm2 are achieved, the highest reported for OPV devices using uAJP AgNW inks as top electrodes.
CRIS-Team Scopus Importer:2025-01-31
Keywords: aerosol jet printing; organic photovoltaics; ultrasonic spray coating